Murilo Mendes: pânico, amor e poesia: uma leitura de A Poesia em Pânico à luz do surrealismo - SALES, Maria Domingas Ferreira de (Universidade Federal do Pará, 2012)
This research privileges, a priori, five concerning important aspects to the influence of the Surrealism in Murilo Mendes's literary production, especially in the Poetry in Panic, such as: the poetic of the construction for roads of the denial; the conciliation of objects and you idealize divergentes that waives for the search of the totality; the double, indirectly linked to the fears of the repression; the woman and the love, as necessary confluences for the establishment of the project of surrealist construction; and the poetry as space of the saving word. Such aspects are in consonance with the studies proposed by André Breton, Ferdinand Alquié, Chénieux-Gendron, Walter Benjamin and other. Related to the production of poets simbolistas and surrealist, the work in focus lets to illustrate for some artistic works of the painter paraense Ismael Nery, with whom Murilo Mendes establishes great friendship, and fragments of such poets' texts like Artur Rimbaud, Charles Baudelaire, Lautréamont, Stéphane Mallarmé, André Breton. Murilo Mendes, for who the ideas don't have borders, was one of the most representative authors of the surrealist writing in Brazil that, although notified here in just one of your works, constitutes permanent line in all your poetic path.